Nation Branding: Beautiful Bangladesh - Tinne, Wahida Shahan (Asian Business Review, 2013)
Recently a word ‘Nation Branding’ or ‘Branding Bangladesh’ is practiced a lot. A nation brand is the total sum of all perceptions of a nation in the mind of international stakeholders which may contain some of the following elements: people, place, culture, language, history, food, fashion, famous faces (celebrities), global brands, etc. The way for a nation to gain a better reputation is to communicate to the international audience that how good you are, is called nation branding. There is a misconception among most of the people that it is required to develop tourism sector of any country in case of nation branding. But nation branding focuses on the nation as a whole – its people, culture and heritage, investment and immigration, governance, exports and tourism. The objective of this paper is to clarify this misconception about nation branding, help our citizens to know about the branding Bangladesh and reveal the possibilities of branding Bangladesh. Process of nation branding –Nation Brand Index and Country Brand Index are discussed in this paper. This research is based on secondary sources and the researcher comes up with the Nation Branding Hexagon for Bangladesh. Hopefully this paper will be helpful for awaking our consumers and making responsible to come forward for unbeaten nation branding for Bangladesh.